2018
DOI: 10.1021/acs.organomet.8b00074
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation Reactions of an Organometallic Ni(I) Amidate Complex: Scope and Mechanistic Investigations

Abstract: The N-heterocyclic carbene supported three-coordinate Ni­(I) complex (IPr)­Ni­(κ1-N-N­( i Pr)­C­(O) t Bu)­(CNXyl) ([2-CNXyl]; CNXyl = 2,6-dimethylphenyl isocyanide) undergoes disproportionation with 1 equiv of CNXyl to afford an equimolar mixture of Ni(0) and Ni­(II) complexes (IPr)­Ni­(CNXyl)3 ([3-CNXyl]) and (IPr)­Ni­(κ2-N,O-N­( i Pr)­CO­( t Bu))2 ([4]), respectively. Complexes [3-CNXyl] and [4] are also produced when 2 equiv of the isonitrile CNXyl is added to (IPr)­Ni­(κ3-N,bis­(H 2 CMe)-N­( i Pr)­C­(O) t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…Lithium chloride 21 can overcome zinc inhibition and was generally the most useful additive studied ( Table 1 , entries 1–6, and Table S2 ). 22 , 23 While we found that reduction of octyl bromide to octylzinc bromide was also inhibited by zinc salts, 21d , 24 reduction of palladium(II) phosphine complexes to palladium(0) was fast with or without added LiCl or Zn ( Figures S11–S16 ). 25 , 26 …”
mentioning
confidence: 87%
“…Lithium chloride 21 can overcome zinc inhibition and was generally the most useful additive studied ( Table 1 , entries 1–6, and Table S2 ). 22 , 23 While we found that reduction of octyl bromide to octylzinc bromide was also inhibited by zinc salts, 21d , 24 reduction of palladium(II) phosphine complexes to palladium(0) was fast with or without added LiCl or Zn ( Figures S11–S16 ). 25 , 26 …”
mentioning
confidence: 87%
“…30,33 We previously reported the linear nickel(I) complexes with pairs of nearly symmetric δ-bis(C-H) contacts from pendant methyl groups that were tentatively assigned as pseudo-bis-agostic complexes based on existing norms for the assignment of such species. 34,35 Herein, we report additional spectroscopic data that correct our original assignment and identify a previously unrecognized mode of bis-agostic interaction that results from direct C-…”
Section: Introductionmentioning
confidence: 57%
“…2a). 34,35 Fig. 2b shows the Ni K-edge pre-edge region for analogous complexes both with (1,3) and without (2,4) bis-agostic interactions: the spectra are strikingly different in this region.…”
Section: Resultsmentioning
confidence: 99%
“…This SET has a barrier of 12.3 kcal mol −1 and the overall process is slightly endergonic, although the low barrier found for the halide abstraction from Ni 0 catalyst will push the reaction again to force the turnover of the catalytic cycle. Although this step is the most likely to close the catalytic cycle and provide the catalytic turnover, other pathways such as Ni I disproportionation may coexist in the reaction media …”
Section: Methodsmentioning
confidence: 99%
“…Finally,t he initial species 1 and the Ru II photoredox catalyst are regenerated by as econd SET.T his SET has ab arrier of 12.3 kcal mol À1 and the overall process is slightly endergonic,a lthough the low barrier found for the halide abstraction from Ni 0 catalyst will push the reaction again to force the turnover of the catalytic cycle.A lthough this step is the most likely to close the catalytic cycle and provide the catalytic turnover, other pathways such as Ni I disproportionation may coexist in the reaction media. [27] We summarize the calculated mechanism of the Ni/Ru catalyzed indoline formation in Scheme 2. Thee lementary steps that can be run without irradiation (upper part of the catalytic cycle) move between Ni 0 ,N i I ,a nd Ni II oxidation states.T hose steps consist of the activation ofiodoacetanilide and alkene substrates,and the formation of aC ÀCbond.…”
mentioning
confidence: 99%